2014
DOI: 10.1177/1359105314521478
|View full text |Cite
|
Sign up to set email alerts
|

How can core self-evaluations influence job burnout? The key roles of organizational commitment and job satisfaction

Abstract: This study aimed to explore how core self-evaluations influenced job burnout and mainly focused on the confirmation of the mediator roles of organizational commitment and job satisfaction. A total of 583 female nurses accomplished the Core Self-Evaluation Scale, Organizational Commitment Scale, Minnesota Satisfaction Questionnaire, and Maslach Burnout Inventory-General Survey. The results revealed that core self-evaluations, organizational commitment, job satisfaction, and job burnout were significantly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 36 publications
9
109
0
6
Order By: Relevance
“…The Chinese version of the MBI-GS has been widely used in Chinese studies and has demonstrated satisfactory reliability and validity (Peng et al, 2014;Wang et al, 2012a;Wu et al, 2007). The internal consistency coefficients for the three subscales ranged from 0.88 to 0.93 in this study.…”
Section: Job Burnoutmentioning
confidence: 60%
“…The Chinese version of the MBI-GS has been widely used in Chinese studies and has demonstrated satisfactory reliability and validity (Peng et al, 2014;Wang et al, 2012a;Wu et al, 2007). The internal consistency coefficients for the three subscales ranged from 0.88 to 0.93 in this study.…”
Section: Job Burnoutmentioning
confidence: 60%
“…On the other, organisational commitment has been confirmed to promote job satisfaction (Li, Early, Mahrer, Klaristenfeld, & Gold, 2014). Organisational commitment, job satisfaction and job burnout were significantly correlated with each other (Peng et al, 2014). Thirdly, the impact of empowerment on organisational commitment has also been confirmed (Laschinger, Finegan, & Wilk, 2009).…”
Section: The Impact Of Psychological Empowerment and Organisational Cmentioning
confidence: 91%
“…H3: Automatic acting positively correlates with mental health and has positive effect on mental health. Burnout refers to the state in which individuals experience physical and mental fatigue after working under heavy pressure [11]. Such concept was first defined in 1974 by Freudenberger [12], who found a series of symptoms in young workers who were volunteers in a clinic.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%